Investigation of the explosive throwing of the two variable thicknesses fragmentary disks - V. V. Fepa; Yu. M. Sydorenko; V. V. Yakovenko (Mechanics and Advanced Technologies, 2017)
The results of the process of explosive throwing of a set of fragmentary disks with the charge of an explosive are given in the work. This set consists of two disks of natural crushing of different thicknesses of a fixed total mass. The research was carried out using the computer simulation of shock-wave processes in the continuous formulation using the ANSYS/LS-DYNA program. The influence of the order of the installation of discs of different thickness on the value of the angle of fragmentation of the fractional mass and the axial velocity of its motion is established.